2016
DOI: 10.1007/s12282-016-0688-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in personalized cancer immunotherapy

Abstract: There are currently three major approaches to T cell-based cancer immunotherapy, namely, active vaccination, adoptive cell transfer therapy and immune checkpoint blockade. Recently, this latter approach has demonstrated remarkable clinical benefits, putting cancer immunotherapy under the spotlight. Better understanding of the dynamics of anti-tumor immune responses (the "Cancer-Immunity Cycle") is crucial for the further development of this form of treatment. Tumors employ multiple strategies to escape from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 58 publications
0
72
0
Order By: Relevance
“…[215] A deeper understanding of tumor immunology and antitumor immune responses is indispensable for further discoveries and innovations of cancer immunotherapy. [220] Recently, neoantigens, or antigens derived from an individual tumor's specific mutations, have been leveraged for personalized cancer immunotherapy. Much like chemotherapy and radiation, the off-target toxicity associated with cancer immunotherapy can be drastic in approaches including vaccines, cytokines, checkpoint blockades, and cell therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[215] A deeper understanding of tumor immunology and antitumor immune responses is indispensable for further discoveries and innovations of cancer immunotherapy. [220] Recently, neoantigens, or antigens derived from an individual tumor's specific mutations, have been leveraged for personalized cancer immunotherapy. Much like chemotherapy and radiation, the off-target toxicity associated with cancer immunotherapy can be drastic in approaches including vaccines, cytokines, checkpoint blockades, and cell therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, each individual tumor must be treated in a personalized manner. [220] Recently, neoantigens, or antigens derived from an individual tumor's specific mutations, have been leveraged for personalized cancer immunotherapy. [18,69,221] With the development of sequencing technology, researchers are able to know the genetic landscape of human cancers, as well as identify specific neoantigens in each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our sequencing and epitope prediction algorithms are similar to those of other investigators: we identified somatic missense mutations through exome sequencing of tumor and normal tissue, followed by expression analysis by RNA sequencing, as many mutations are not expressed. Our final step towards identification of candidate neoantigens involved the use of computer algorithms that predict which mutations can give rise to peptides that can be presented by the patient’s HLA alleles (30,35,36). Preclinical studies performed to date suggest that the majority of candidate neoantigens, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, medical advances have led to the discovery and successful clinical implementation of several classes of immunotherapy against cancer, including vaccination, adoptive cell transfer, and immune checkpoint inhibitors (ICIs) . Several ICIs, including ipilimumab (an antibody targeting cytotoxic T lymphocyte associated antigen 4, CTLA‐4), nivolumab, pembrolizumab, and cemiplimab (antibodies directed against the programmed cell death 1, PD‐1), atezolizumab, durvalumab, and avelumab (anti‐PD‐1 ligand, PD‐L1), have led to improved survival in patients with various cancer types including lung, kidney, liver, bladder and breast cancer, melanoma and lymphomas .…”
Section: Introductionmentioning
confidence: 99%